Legal construction of interest rate determination in information technology-based lending services in Indonesia - Fauzi, Engrina; Azheri, Busyra; Hasbi, M.; Mulyati, Nani (Linguistics and Culture Review, 2021)
There is a legal vacuum regarding determining loan interest rates in Article 17 paragraph (1) POJK No. 77/01/2016 concerning Information Technology-Based Lending and Borrowing Services (ITBLBS). With this legal vacuum, O.J.K. has given the authority to AFPI to self-regulate the determination of loan interest rates at ITBLBS. With authority as an S.R.O. ( Self Regulating Organization ) institution owned by the Indonesian Joint Funding Fintech Association (IJFFA). The method used is normative legal research by analyzing primary, secondary, and tertiary legal materials related to the research title. The interest rate in the code of conduct that IFFFA determines as the principle of operation in ITBLBS directly affects the inflation rate. However, Bank Indonesia, as the institution authorized and responsible for targeting inflation in terms of controlling interest rates circulating in the fintech market, is not given any authority based on Article 17 POJK N0. 77 of 2016. This is in contrast to the inflation targeting objective, which is the authority of B.I. It can be concluded that the determination of interest rates in the existing ITBLBS is normatively out of sync between the objectives of the legislation and the objectives of the IJFFA code of conduct.